Enacting Gender: An Enactive-Ecological Account of Gender and Its Fluidity - Albarracin, Mahault; Poirier, Pierre (Frontiers in Psychology, 2022)
This paper aims to show that genders are enacted, by providing an account of how an individual can enact a gender and genders can be fluid. On the enactive-ecological view we defend, individuals perceive the world as fields of affordances. Fields of natural affordances offer action possibilities because of the natural properties of organisms and environments. Although humans live in fields of bodily, action, and cultural affordances, our work focuses on cultural affordances, where action possibilities are offered to individuals because of the normative responses of individuals in that culture.. Usually, behaving normatively in response to cultural affordances brings about sequences of perception-action loops, which we will call “scripts”: for instance, closed doors afford knocking, which affords the individual inside opening the door, which affords an interpersonal meeting, which (may) afford entrance. Although the notion of script has a strong cognitivist flavour, one of the aims of the paper to provide an ecological account of scripts, to show that what cognitivists such as Schank and Abelson (1977) viewed as representations (or representational structures) are in fact environmentally structured perception-action loops. On our account of gender, gendered cultures build and maintain gendered cultural affordance landscapes, that is, landscapes in which the action possibilities individuals face are normed according to a specific body type or situation; most often (assigned) biological sex. Individuals enact a given gender when they come to perceive the affordances reserved for one gender by their culture and respond in the culturally normative way, thus enacting gendered sequences of perception-action loops (i.e., gendered scripts). With the shifting landscapes of cultural affordances brought about by several recent social, technological, and epistemic developments in some cultures, the gendered landscapes of affordances offered to individuals in these cultures have become more varied and less rigid, thus increasing the variety and flexibility of scripts individuals can enact. This entails that individuals in such cultures have an increased possibility for gender fluidity, which may in part explain the increasing number of people currently identifying outside the binary.